2023
DOI: 10.3389/fimmu.2023.1102912
|View full text |Cite
|
Sign up to set email alerts
|

Cell morphology as a biological fingerprint of chondrocyte phenotype in control and inflammatory conditions

Abstract: IntroductionLittle is known how inflammatory processes quantitatively affect chondrocyte morphology and how single cell morphometric data could be used as a biological fingerprint of phenotype.MethodsWe investigated whether trainable high-throughput quantitative single cell morphology profiling combined with population-based gene expression analysis can be used to identify biological fingerprints that are discriminatory of control vs. inflammatory phenotypes. The shape of a large number of chondrocytes isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 108 publications
(164 reference statements)
0
23
0
Order By: Relevance
“…To determine if there were quantitative significant differences in shape descriptors (area, length, width, circularity, aspect ratio, roundness, and solidity), single-cell macrophage analysis was performed using a Fiji-based analysis algorithm ( 13 , 29 ). When comparing different groups of macrophages, the violin box plots ( Figure 5 ) revealed that the GM-CSF/TNFα/IFNγ-M1 (largest) and GM-CSF-M1 macrophages were larger in cell area than the other groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine if there were quantitative significant differences in shape descriptors (area, length, width, circularity, aspect ratio, roundness, and solidity), single-cell macrophage analysis was performed using a Fiji-based analysis algorithm ( 13 , 29 ). When comparing different groups of macrophages, the violin box plots ( Figure 5 ) revealed that the GM-CSF/TNFα/IFNγ-M1 (largest) and GM-CSF-M1 macrophages were larger in cell area than the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…The panel of morphological descriptors that we used here was successfully used by our group to phenotype differentiated human mesenchymal stromal cells (MSCs) ( 30 33 ) and healthy vs. inflamed and degenerating diseased human chondrocytes ( 13 ). Moreover, using this panel as a phenotypic marker, combined with multivariate data analysis, we showed that the cell morphology and phenotype, i.e., the “biological fingerprint” of those inflamed and degenerated diseased human cells could be reverted to a healthier cell shape via therapeutic modulation and their healthier cell shape correlated with positive changes in major fibrosis- and inflammatory-regulating genes ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification results of CCK-8 revealed that the proliferative activity of cells on CT-C was significantly higher than that of the Control (Figure B). Since the cell shape is strongly coupled with cell growth, the cell area, the aspect ratio, and roundness were also determined. , As shown in Figure A-ii, the cell area of CT-C was significantly higher than that of Control on the fifth day (Figure C), suggesting that the CT-C could promote cell spreading with the extension of culturing time. The cell aspect ratio (Figure D) in the CT-C group was significantly higher, while the roundness (Figure E), which is related to cell proliferation, was significantly lower.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM image in Figure 9 indicates chondrocytes cultured in HA–CPN for 28 days were embedded within the secreted ECM, and the cells can retain the correct phenotypes. Instead of an elongated morphology on TCPS due to the dedifferentiation of the chondrocytes, chondrocytes in HPN maintain a spherical morphology, which is one of the characteristics of differentiated chondrocytes [ 47 ]. The dedifferentiation of chondrocytes is common after an in vitro cell culture on TCPS, where chondrocytes tend to lose the original morphology and show a diffused actin network with pronounced stress fiber formation [ 47 ].…”
Section: Resultsmentioning
confidence: 99%